Solar cells and photoelectric conversion elements

By using a carbon-based porous electron transport layer in solar cells, the fixing power is enhanced, addressing the issue of peeling and ensuring efficient photoelectric conversion, even on uneven surfaces.

JP7656838B2Active Publication Date: 2025-04-04PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2022534987
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-06
Filing Date
2021-06-16
Publication Date
2025-04-04
Estimated Expiration
2041-06-16

AI Technical Summary

Technical Problem

Existing solar cells face challenges in maintaining the integrity of the electron transport layer, particularly on surfaces with uneven structures, which can lead to peeling and reduced photoelectric conversion efficiency.

Method used

The solar cell design incorporates a first electron transport layer made of carbon and a porous electron transport material, which enhances the fixing power and prevents peeling, ensuring a uniform photoelectric conversion layer across the surface.

Benefits of technology

This configuration significantly improves the photoelectric conversion efficiency by maintaining the integrity of the electron transport layer, even on surfaces with concave and convex structures, thereby preventing short circuits and ensuring reliable solar cell performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656838000004
    Figure 0007656838000004
  • Figure 0007656838000005
    Figure 0007656838000005
  • Figure 0007656838000006
    Figure 0007656838000006
Patent Text Reader

Abstract

A solar cell 100 is provided with a first electrode 2, a first electron transportation layer 4, a second electron transportation layer 3, a photoelectric conversion layer 5, and a second electrode 7. The first electron transportation layer 4 includes a porous electron-transportation material and carbon.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a solar cell and a photoelectric conversion element. [Background technology]

[0002] In recent years, research and development of organic thin-film solar cells or perovskite solar cells has been progressing as new solar cells to replace existing silicon-based solar cells.

[0003] Perovskite solar cells use a perovskite compound represented by the chemical formula ABX3 (where A is a monovalent cation, B is a divalent cation, and X is a halogen anion) as a photoelectric conversion material.

[0004] Non-Patent Document 1 discloses a perovskite solar cell in which a perovskite compound represented by the chemical formula CH3NH3PbI3 (hereinafter referred to as "MAPbI3") is used as the photoelectric conversion material of the perovskite solar cell. In the perovskite solar cell disclosed in Non-Patent Document 1, the perovskite compound represented by MAPbI3, TiO2, and Spiro-OMeTAD are used as the photoelectric conversion material, electron transport material, and hole transport material, respectively.

[0005] Non-Patent Document 2 uses CH3NH3 as a photoelectric conversion material for perovskite solar cells. + (hereinafter referred to as "MA"), CH(NH2)2 + (hereinafter referred to as "FA") and a perovskite solar cell using a multi-cation perovskite compound having Cs as a monovalent cation. In the perovskite solar cell disclosed in Non-Patent Document 2, a multi-cation perovskite compound, TiO2, and Spiro-OMeTAD are used as a photoelectric conversion material, an electron transport material, and a hole transport material, respectively.

[0006] Patent Document 1 discloses an organic thin-film solar cell. The organic thin-film solar cell disclosed in Patent Document 1 has an uneven microstructure at the interface between the photoelectric conversion layer and the electrode. Due to this configuration, the organic thin-film solar cell disclosed in Patent Document 1 can improve the photoelectric energy conversion efficiency. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2014 / 208713 [Non-patent literature]

[0008] [Non-Patent Document 1] Julian Burschka et al., “Sequential deposition as a route to high-performance perovskite-sensitized solar cells”, Nature, vol.499, pp.316-319, 18 July 2013 [DOI:10.1038 / nature12340] [Non-Patent Document 2] Taisuke Matsui et al., “Room‐Temperature Formation of Highly Crystalline Multication Perovskites for Efficient, Low‐Cost Solar Cells”, Advanced Materials, Volume29, Issue15, April 18, 2017, 1606258 [DOI:10.1002 / adma.201606258] [Non-Patent Document 3] Qingfeng Dong et al., Science, 2015, 347, 6225, 967-970 Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present disclosure is to provide a solar cell having an improved anchoring power of an electron transport layer. [Means for solving the problem]

[0010] The solar cell according to the present disclosure comprises: first electrode, a first electron transport layer; second electron transport layer, A photoelectric conversion layer, and second electrode, Equipped with Where: the photoelectric conversion layer is provided between the first electrode and the second electrode, the first electron transport layer is provided between the photoelectric conversion layer and the first electrode, the second electron transport layer is provided between the first electron transport layer and the first electrode, The first electron transport layer includes carbon and a porous electron transport material. Effect of the Invention

[0011] The present disclosure provides a solar cell having an improved anchoring power of an electron transport layer. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 shows a cross-sectional view of a solar cell 100 according to a first embodiment. [Diagram 2] FIG. 2 shows a cross-sectional view of a solar cell 200 according to a first embodiment. [Figure 3A] FIG. 3A is a diagram illustrating convex portions of the concave-convex structure in solar cell 200 according to the first embodiment. [Figure 3B] FIG. 3B is a diagram illustrating recesses in the relief structure of solar cell 200 according to the first embodiment. [Figure 3C] FIG. 3C is a diagram illustrating the height difference of the projections and recesses of the projection-recess structure in the solar cell 200 according to the first embodiment. [Figure 4]FIG. 4 shows a cross-sectional view of a solar cell 300 according to a second embodiment. [Diagram 5] FIG. 5 shows a cross-sectional view of a photoelectric conversion layer-attached substrate 400 according to the first embodiment. [Figure 6] FIG. 6 is a graph showing the carbon profile obtained by time-of-flight secondary ion mass spectrometry for the first electron transport layer of Example 1. [Figure 7A] FIG. 7A is a graph showing the results of estimating the relationship between the carbon threshold and normalized efficiency in solar cells fabricated on a flat substrate or a textured substrate having an uneven surface. [Figure 7B] FIG. 7B is a graph showing the relationship between calcination temperature and carbon threshold. [Figure 8] FIG. 8 is a graph showing the UV irradiation time dependence of the C-C bond peak intensity for the first electron transport layer of Example 1, which was determined from the change in intensity of the C1s spectrum obtained by X-ray photoelectron spectroscopy. [Figure 9] FIG. 9 is a graph showing the baking temperature dependence of the film thickness before and after spin-coating with a solvent after baking the first electron transport layer disposed on a flat substrate. [Figure 10A] FIG. 10A is a graph showing the firing temperature dependence of the open circuit voltage of a solar cell fabricated using a flat substrate after firing a first electron transport layer disposed on the substrate. [Figure 10B] FIG. 10B is a graph showing the firing temperature dependence of the short-circuit current density of a solar cell fabricated using a flat substrate after firing a first electron transport layer disposed on the substrate. [Figure 10C] FIG. 10C is a graph showing the sintering temperature dependence of the fill factor of a solar cell fabricated using a flat substrate after sintering a first electron transport layer disposed on the substrate. [Figure 10D] FIG. 10D is a graph showing the sintering temperature dependence of the conversion efficiency of a solar cell fabricated using a flat substrate after sintering a first electron transport layer disposed on the substrate. [Figure 11A]FIG. 11A is a graph showing the results of estimating solar cell performance when the horizontal axis of FIG. 10A is converted into the carbon threshold and short circuits between layers that occur in regions with low carbon threshold are taken into consideration. [Figure 11B] FIG. 11B is a graph showing the results of estimating solar cell performance when the horizontal axis of FIG. 10B is converted into the carbon threshold and short circuits between layers that occur in regions with low carbon threshold are taken into consideration. [Figure 11C] FIG. 11C is a graph showing the results of estimating solar cell performance when the horizontal axis of FIG. 10C is converted into the carbon threshold and short circuits between layers that occur in regions with low carbon threshold are taken into consideration. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] <Terminology> As used herein, the term "perovskite compound" refers to a perovskite crystal structure represented by the chemical formula ABX3 (wherein A is a monovalent cation, B is a divalent cation, and X is a halogen anion) and structures having crystals similar thereto.

[0014] The term "perovskite solar cell" as used in this specification means a solar cell that contains a perovskite compound as a photoelectric conversion material.

[0015] <Knowledge that formed the basis of this disclosure> The findings that form the basis of this disclosure are described below.

[0016] As disclosed in Non-Patent Document 3, perovskite compounds have characteristic physical properties of a high light absorption coefficient and a long diffusion length. Due to these physical properties, perovskite solar cells can generate electricity efficiently with a thickness of several hundred nanometers. Furthermore, perovskite solar cells have the characteristics of using less material than existing silicon solar cells, not requiring high temperatures in the formation process, and being able to be formed by coating. Due to this characteristic, perovskite solar cells can be formed on a substrate made of a lightweight and flexible material such as plastic. Therefore, perovskite solar cells can be installed in areas where weight restrictions have been imposed until now. For example, perovskite solar cells can be developed into building material-integrated solar cells in combination with existing materials, such as building materials. In such a case where a perovskite solar cell is constructed in combination with a building material, for example, a member having a relatively large uneven structure on the surface is used as a substrate, and the perovskite solar cell needs to be formed on the substrate.

[0017] In addition, in order to further increase the photoelectric conversion efficiency, a stacked solar cell in which a perovskite solar cell and a silicon solar cell are stacked, i.e., a tandem solar cell, is being considered. In order to effectively utilize the incident light, a silicon solar cell may have a textured structure with unevenness on the surface. Therefore, when a silicon solar cell has a textured structure, the perovskite solar cell needs to be formed on the surface having the uneven structure without peeling.

[0018] If peeling occurs during coating and film formation of a perovskite solar cell, the substrate penetrates the perovskite solar cell at the peeled portion, causing a short circuit with the upper electrode, resulting in a decrease in power generation efficiency. As a result, the solar cell may no longer function. The present inventors have found that if the solvent-philic porous electron transport peels off during the manufacture of a perovskite solar cell, the capillary force of the solution of the photoelectric conversion layer does not work in the subsequent process, and a portion without the photoelectric conversion layer may be generated.

[0019] For example, in the case of a tandem solar cell, the thickness of the perovskite solar cell is smaller than the average height of the uneven structure of the texture, and the film is formed by coating. Therefore, if the adhesion to the uneven structure is weak, the convex parts of the substrate will be exposed, and the formation of the perovskite solar cell on the entire surface will be insufficient. In other words, the perovskite solar cell will be missing at the convex parts, and the substrate will penetrate the perovskite solar cell and short-circuit with the upper electrode. As a result, the perovskite solar cell will no longer function.

[0020] In view of these findings, the present inventors have discovered a structure that enables the fabrication of a perovskite solar cell in which a new solvent-based porous electron transport layer is disposed without peeling over the entire area that requires the solution to adhere until the formation of the perovskite solar cell is complete, such as a surface having an uneven structure or a surface with a three-dimensional structure. Furthermore, the inventors have discovered that this structure can improve the photoelectric conversion efficiency even when the solar cell is formed on a flat surface.

[0021] <Embodiments of the present disclosure> Hereinafter, embodiments of the present disclosure will be described in detail with reference to the drawings.

[0022] (First embodiment) FIG. 1 shows a cross-sectional view of a solar cell 100 according to a first embodiment.

[0023] 1, the solar cell 100 according to the first embodiment includes a substrate 1, a first electrode 2, a second electron transport layer 3, a first electron transport layer 4, a photoelectric conversion layer 5, a hole transport layer 6, and a second electrode 7. Specifically, the substrate 1, the first electrode 2, the second electron transport layer 3, the first electron transport layer 4, the photoelectric conversion layer 5, the hole transport layer 6, and the second electrode 7 are provided in this order. The first electron transport layer 4 has a first main surface 4a (i.e., the first main surface facing the photoelectric conversion layer 5) and a second main surface 4b (i.e., the second main surface facing the first electron transport layer 3).

[0024] The first electron transport layer 4 contains carbon and a porous electron transport material.

[0025] In the solar cell 100, the first electron transport layer 4 contains carbon and therefore has high adhesion. As a result, peeling of the first electron transport layer due to non-uniform solution flow does not occur in the coating and drying step, and peeling during the subsequent formation of the photoelectric conversion layer can be prevented.

[0026] A layer having another function may be provided between the substrate 1 and the first electrode 2, between the first electrode 2 and the second electron transport layer 3, between the photoelectric conversion layer 5 and the hole transport layer 6, or between the hole transport layer 6 and the second electrode.

[0027] An example of the above-mentioned "layer having another function" is, for example, a layer having a function of suppressing charge recombination at an interface.

[0028] The first electrode 2 may have an uneven structure.

[0029] FIG. 2 shows a cross-sectional view of a solar cell 200 according to a first embodiment.

[0030] 2, a solar cell 200 according to the second embodiment includes a substrate 1, a first electrode 2, a second electron transport layer 3, a first electron transport layer 4, a photoelectric conversion layer 5, a hole transport layer 6, and a second electrode 7. Specifically, the substrate 1, the first electrode 2, the second electron transport layer 3, the first electron transport layer 4, the photoelectric conversion layer 5, the hole transport layer 6, and the second electrode 7 are provided in this order. The first electron transport layer 4 has a first main surface 4a (i.e., the first main surface facing the photoelectric conversion layer 5) and a second main surface 4b (i.e., the second main surface facing the first electron transport layer 3).

[0031] The first electrode 2 has a first main surface 2a facing the second electron transport layer 3. The first main surface 2a has an uneven structure. The second electron transport layer 3, the first electron transport layer 4, the photoelectric conversion layer 5, the hole transport layer 6, and the second electrode 7 provided on the first main surface 2a of the first electrode 2 have an uneven structure that reflects the uneven structure of the first main surface 2a that serves as the base. In the solar cell 100, the first electrode 2 is provided on the first main surface 1a of the substrate 1. The first main surface 1a of the substrate 1 has an uneven structure. That is, the uneven structure of the first main surface 2a of the first electrode 2 reflects the uneven structure of the first main surface a of the substrate 1 that serves as the base.

[0032] In this specification, the term "uneven structure" refers to surface unevenness observed in a cross-sectional image taken with a scanning transmission electron microscope, in which the average height difference between the convex and concave portions exceeds 0.1 μm.

[0033] The "protrusions" and "recesses" of the uneven structure in this specification will be described. FIG. 3A is a diagram illustrating the protrusions of the uneven structure in the solar cell 200 according to the first embodiment. FIG. 3B is a diagram illustrating the recesses of the uneven structure in the solar cell 200 according to the first embodiment. FIG. 3C is a diagram illustrating the height difference of the unevenness of the uneven structure in the solar cell 200 according to the first embodiment. The protrusions refer to the apex of the convex shape of the uneven structure and its surrounding portion as shown in FIG. 3A. The surrounding portion of the apex is, for example, a region that includes a middle height or more between the apex and the bottom of the adjacent concave shape based on the apex. The recesses refer to the bottom of the concave shape of the uneven structure and its surrounding portion as shown in FIG. 3B. The surrounding portion of the bottom of the concave shape is, for example, a region that includes a middle height or less between the apex of the adjacent convex shape based on the bottom of the concave shape. The height difference of the uneven structure is the height from the apex of the convex portion to the bottom of the concave portion as shown in FIG. 3C, and can take various values ​​depending on the location (for example, height difference A, height difference B, etc. in the figure). The difference in the uneven structure is expressed by the average value of the height difference of the uneven structure. Here, the average value of the height difference between the convex portion and the concave portion is calculated as follows. First, a cross-sectional image of a scanning transmission electron microscope is used, and an arbitrary region of 20 μm in length is extracted from the cross-sectional image. Next, for the surface unevenness of that region, all the height differences between adjacent convex portions and concave portions are measured. The average value of the height difference is calculated from the obtained measured values. In this manner, the average value of the height difference between the convex portions and the concave portions is calculated.

[0034] The average height difference between the convex portions and the concave portions of the concave-convex structure of the first electrode 2 in the solar cell 200 may be 0.5 μm or more and 3 μm or less.

[0035] Each layer will be described in detail below with reference to FIG.

[0036] (Substrate 1) The substrate 1 holds each layer constituting the solar cell 200. As shown in FIG. 1, the substrate 1 may have an uneven structure on a first main surface 1a facing the first electrode 2. The substrate 1 may be made of a transparent material. Examples of the base material 1 are a glass substrate and a plastic substrate. The plastic substrate may be a plastic film. If the first electrode 2 has sufficient strength to hold each layer, the solar cell 200 may not include the substrate 1.

[0037] (1st electrode 2) The first electrode 2 is conductive. As described above, the first main surface 2a of the first electrode 2 may have an uneven structure.

[0038] The solar cell 200 includes a second electron transport layer 3 and a first electron transport layer 4 between the first electrode 2 and the photoelectric conversion layer 5. For this reason, the first electrode 2 does not need to have the property of blocking holes moving from the photoelectric conversion layer 5. The first electrode 2 may be made of a material capable of forming an ohmic contact with the photoelectric conversion layer 5.

[0039] The first electrode 2 may or may not have light-transmitting properties. At least one selected from the group consisting of the first electrode 2 and the second electrode 7 has light-transmitting properties. The first electrode 2 transmits light in the range from visible to near infrared, for example.

[0040] The first electrode 2 may be made of, for example, a transparent and conductive material. Such a material may be, for example, at least one selected from the group consisting of metal oxides and metal nitrides. Examples of such materials include: (i) titanium oxide doped with at least one selected from the group consisting of lithium, magnesium, niobium, and fluorine; (ii) gallium oxide doped with at least one element selected from the group consisting of tin and silicon; (iii) gallium nitride doped with at least one selected from the group consisting of silicon and oxygen; (iv) indium-tin composite oxide, (v) tin oxide doped with at least one element selected from the group consisting of antimony and fluorine; (vi) zinc oxide doped with at least one element selected from the group consisting of boron, aluminum, gallium, and indium, or (vii) any combination of these It is.

[0041] The first electrode 2 may be an electrode made of a non-transparent material and having a pattern shape that allows light to pass through. Examples of the pattern shape that allows light to pass through include a line shape, a wavy line shape, a lattice shape, or a punched metal shape in which a large number of fine through holes are regularly or irregularly arranged. The first electrode 2 having the above pattern shape allows light to pass through the part of the electrode where no electrode material is present. Examples of non-transparent materials are platinum, gold, silver, copper, aluminum, rhodium, indium, titanium, iron, nickel, tin, zinc, or an alloy containing any of these. The material may be a carbon material having electrical conductivity.

[0042] The light transmittance of the first electrode 2 may be, for example, 50% or more, or 80% or more. The wavelength of light transmitted through the first electrode 2 depends on the absorption wavelength of the photoelectric conversion layer 5. The first electrode 2 may have a thickness of, for example, 1 nm or more and 1000 nm or less.

[0043] (Second electron transport layer 3) The second electron transport layer 3 includes a semiconductor. The second electron transport layer 3 may be formed of a semiconductor having a band gap of 3.0 eV or more. By forming the second electron transport layer 3 with a semiconductor having a band gap of 3.0 eV or more, visible light and infrared light can be transmitted to the photoelectric conversion layer 5. Examples of the semiconductor include organic or inorganic n-type semiconductors.

[0044] Examples of organic n-type semiconductors are imide compounds, quinone compounds, fullerenes, or fullerene derivatives. Examples of inorganic n-type semiconductors are oxides of metal elements, nitrides of metal elements, or perovskite oxides. Examples of oxides of metal elements include oxides of Cd, Zn, In, Pb, Mo, W, Sb, Bi, Cu, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga, Si, and Cr. A more specific example is TiO2. Examples of nitrides of metal elements include GaN. Examples of perovskite oxides include SrTiO3 and CaTiO3.

[0045] The second electron transport layer 3 may be formed of a material having a band gap larger than 6.0 eV. Examples of materials having a band gap larger than 6.0 eV include: (i) Alkali metal or alkaline earth metal halides, such as lithium fluoride or barium fluoride; (ii) an oxide of an alkaline earth metal, such as magnesium oxide; or (iii) Silicon dioxide In this case, in order to ensure the electron transporting property of the second electron transport layer 3, the thickness of the second electron transport layer 3 may be, for example, 10 nm or less.

[0046] The second electron transport layer 3 may include a plurality of layers made of different materials.

[0047] (First electron transport layer 4) The first electron transport layer 4 includes a porous electron transport material. Hereinafter, the porous electron transport material is referred to as a porous body. The first electron transport layer 4 may be composed of a porous body.

[0048] The porous body includes pores. The pores are connected from the second main surface 4b of the first electron transport layer 4 in contact with the second electron transport layer 3 to the first main surface 4a of the first electron transport layer 4 in contact with the photoelectric conversion layer 5. The pores are typically filled with a material constituting the photoelectric conversion layer 5, and electrons can move directly from the photoelectric conversion layer 5 to the second electron transport layer 3.

[0049] The porous body is, for example, composed of a series of insulator or semiconductor particles. Examples of insulator particles are aluminum oxide particles or silicon oxide particles. Examples of semiconductor particles are inorganic semiconductor particles. Examples of inorganic semiconductors are oxides of metal elements, perovskite oxides of metal elements, sulfides of metal elements, or metal chalcogenides. Examples of oxides of metal elements are oxides of metal elements such as Cd, Zn, In, Pb, Mo, W, Sb, Bi, Cu, Hg, Ti, Ag, Mn, Fe, V, Sn, Zr, Sr, Ga, Si, or Cr. A specific example of an oxide of a metal element is TiO2. Examples of perovskite oxides of metal elements are SrTiO3 or CaTiO3. Examples of sulfides of metal elements are CdS, ZnS, In2S3, PbS, Mo2S, WS2, Sb2S3, Bi2S3, ZnCdS2, or Cu2S. Examples of metal chalcogenides are CdSe, In2Se3, WSe2, HgS, PbSe, or CdTe.

[0050] The first electron transport layer 4 contains carbon. Carbon may be contained as a constituent element of the first electron transport layer 4.

[0051] The carbon contained in the first electron transport layer 4 may be derived from, for example, a binder used when forming the porous body. The binder may be, for example, a dispersant such as a surfactant attached to the surface of particles used when forming the porous body, or an organic compound used for the purpose of strengthening the bond between the porous body and a layer serving as a base (for example, the second electron transport layer 3). The porous body can serve as a base when the photoelectric conversion layer 5 is formed. By using a binder, the porous body can be firmly bonded even on the convex parts of a surface having an uneven structure. Therefore, when the photoelectric conversion layer 5 is formed by coating on the porous body, the photoelectric conversion layer 5 can be formed on the surface having an uneven structure.

[0052] In the first electron transport layer 4, the ratio of the second carbon intensity by time-of-flight secondary ion mass spectrometry at the second main surface 4b to the first carbon intensity by time-of-flight secondary ion mass spectrometry at the first main surface 4a (i.e., second carbon intensity / first carbon intensity) may be 0.41 or more and 1.07 or less. Hereinafter, "time-of-flight secondary ion mass spectrometry" is referred to as "TOF-SIMS". In the first electron transport layer 4, sufficient carbon is present in the second main surface 2b such that the second carbon intensity / first carbon intensity satisfies the above range. This increases the fixing power of the first electron transport layer 4, so that the first electron transport layer 4 does not peel off from the substrate, and when the photoelectric conversion layer 5 is formed by coating, the photoelectric conversion layer 5 can be formed to cover the entire surface of the substrate with a substantially uniform film thickness. As a result, a highly reliable solar cell is obtained that is less susceptible to problems such as short circuiting between the substrate and the upper electrode.

[0053] In order to further increase the anchoring power of the first electron transport layer 4, the carbon intensity ratio may be 0.49 or more and 0.90 or less.

[0054] The thickness of the first electron transport layer 4 may be 0.01 μm or more and 10 μm or less, 0.01 μm or more and 1 μm or less, or 0.01 μm or more and 0.2 μm or less. The thickness of the first electron transport layer 4 is, for example, greater than the thickness of the second electron transport layer 3. The first electron transport layer 4 may have a large surface roughness. Specifically, the surface roughness coefficient of the first electron transport layer 4 given by the value of effective area / projected area may be 10 or more, or may be 100 or more. The projected area is the area of ​​a shadow formed behind an object when the object is illuminated with light from the front. The effective area is the actual surface area of ​​the object. The effective area can be calculated from the volume obtained from the projected area and thickness of the object, and the specific surface area and bulk density of the material constituting the object.

[0055] (Photoelectric conversion layer 5) The photoelectric conversion layer 5 contains a perovskite compound. That is, the photoelectric conversion layer 5 contains a perovskite compound composed of monovalent cations, divalent cations, and halogen anions as a photoelectric conversion material. The photoelectric conversion material is a light absorbing material.

[0056] In this embodiment, the perovskite compound may be a compound represented by the chemical formula ABX3, where A is a monovalent cation, B is a divalent cation, and X is a halogen anion.

[0057] In accordance with the terminology commonly used for perovskite compounds, A, B, and X are also referred to herein as the A site, B site, and X site, respectively.

[0058] In this embodiment, the perovskite compound may have a perovskite-type crystal structure represented by the chemical formula ABX3. As an example, a monovalent cation is located at the A site, a divalent cation is located at the B site, and a halogen anion is located at the X site.

[0059] (A Site) The monovalent cation located at the A site is not limited. Examples of monovalent cations are organic cations or alkali metal cations. Examples of organic cations are methylammonium cation (i.e., CH3NH3 + ), formamidinium cation (i.e., NH2CHNH2 + ), phenylethylammonium cation (i.e., C6H5C2H4NH3 + ), or guanidinium cation (i.e., CH6N3 + ). An example of an alkali metal cation is the cesium cation (i.e., Cs + ).

[0060] For high photoelectric conversion efficiency, the A site is, for example, Cs + , formamidinium cation and methylammonium cation may be included.

[0061] The cations constituting the A site may be a mixture of the above-mentioned organic cations, or the cations constituting the A site may be a mixture of at least one of the above-mentioned organic cations and at least one of the above-mentioned metal cations.

[0062] (B Site) The divalent cation located at the B site is not limited. Examples of the divalent cation are divalent cations of elements in Groups 13 to 15. For example, the B site may be a Pb cation, i.e., Pb 2+ or Sn cations, i.e. Sn 2+ may include:

[0063] (X Site) The halogen anion located at the X site is not limited.

[0064] The elements, ie, ions, located at each of the A, B, and X sites may be of one type or of multiple types.

[0065] The photoelectric conversion layer 5 may contain a material other than the photoelectric conversion material. For example, the photoelectric conversion layer 5 may further contain a quencher substance for reducing the defect density of the perovskite compound. The quencher substance is a fluorine compound such as tin fluoride. The molar ratio of the quencher substance to the photoelectric conversion material may be 5% or more and 20% or less.

[0066] The photoelectric conversion layer 5 may mainly contain a perovskite compound composed of monovalent cations, divalent cations, and halogen anions.

[0067] The sentence "photoelectric conversion layer 5 mainly contains a perovskite compound composed of monovalent cations, divalent cations, and halogen anions" means that photoelectric conversion layer 5 contains 70 mass % or more (preferably 80 mass % or more) of a perovskite compound composed of monovalent cations, divalent cations, and halogen anions.

[0068] The photoelectric conversion layer 5 may contain impurities. The photoelectric conversion layer 5 may further contain a compound other than the above-mentioned perovskite compound.

[0069] The photoelectric conversion layer 5 may have a thickness of 50 nm or more and 10 μm or less. The thickness of the photoelectric conversion layer 5 may depend on the magnitude of light absorption of the photoelectric conversion layer 5. A part of the material of the photoelectric conversion layer 5 is filled in the pores of the porous body of the first electron transport layer 4. That is, the photoelectric conversion layer 5 is partially mixed with the first electron transport layer 5. Therefore, the thickness of the photoelectric conversion layer 5 is measured including the photoelectric conversion material filled in the pores of the porous body of the first electron transport layer 4, and includes the thickness of the first electron transport layer 4, for example.

[0070] The perovskite layer included in the photoelectric conversion layer 5 can be formed by using a solution coating method, a co-evaporation method, or the like.

[0071] The photoelectric conversion layer 5 may have an uneven structure. When the photoelectric conversion layer 5 is formed on the first main surface 4a of the first electron transport layer 4, the uneven structure of the photoelectric conversion layer 5 may be formed by following the shape of the uneven structure of the first main surface 4a of the first electron transport layer 4.

[0072] (Hole transport layer 6) The hole transport layer 6 contains a hole transport material. A hole transport material is a material that transports holes. Examples of hole transport materials are organic or inorganic semiconductors.

[0073] Representative examples of organic materials used as hole transport materials include 2,2',7,7'-tetrakis-(N,N-di-p-methoxyphenylamine)9,9'-spirobifluorene (hereinafter referred to as "spiro-OMeTAD"), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (hereinafter referred to as "PTAA"), poly(3-hexylthiophene-2,5-diyl) (hereinafter referred to as "P3HT"), poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (hereinafter referred to as "PEDOT:PSS"), or copper phthalocyanine (hereinafter referred to as "CuPc").

[0074] Inorganic semiconductors are p-type semiconductors. Examples of inorganic semiconductors are Cu2O, CuGaO2, CuSCN, CuI, and NiO. x , MoO x , V2O5, or carbon materials such as graphene oxide.

[0075] The hole transport layer 6 may include a plurality of layers formed from different materials.

[0076] The thickness of the hole transport layer 6 is preferably 1 nm or more and 1000 nm or less, more preferably 10 nm or more and 500 nm or less, and even more preferably 10 nm or more and 50 nm or less. If the thickness of the hole transport layer 6 is 1 nm or more and 1000 nm or less, sufficient hole transport properties can be exhibited. Furthermore, if the thickness of the hole transport layer 5 is 1 nm or more and 1000 nm or less, the resistance of the hole transport layer 5 is low, so that light is converted to electricity with high efficiency.

[0077] The hole transport layer 6 may contain a supporting electrolyte and a solvent. The supporting electrolyte and the solvent can stabilize holes in the hole transport layer 6.

[0078] Examples of supporting electrolytes are ammonium salts or alkali metal salts. Examples of ammonium salts are tetrabutylammonium perchlorate, tetraethylammonium hexafluorophosphate, imidazolium salts, or pyridinium salts. Examples of alkali metal salts are LiN(SO2C n F 2n+1 )2, LiPF6, LiBF4, lithium perchlorate, and potassium boron tetrafluoride.

[0079] The solvent contained in the hole transport layer 6 may have high ionic conductivity. Examples of the solvent are aqueous solvents or organic solvents. From the viewpoint of stabilizing the solute, the solvent may be an organic solvent. Examples of the organic solvent are heterocyclic solvents such as tert-butylpyridine, pyridine, or n-methylpyrrolidone.

[0080] The solvent that may be included in the hole transport layer 6 may be an ionic liquid. The ionic liquid may be used alone or in a mixture with other solvents. The advantages of the ionic liquid are low volatility and high flame retardancy.

[0081] Examples of ionic liquids are imidazolium compounds such as 1-ethyl-3-methylimidazolium tetracyanoborate, pyridine compounds, cycloaliphatic amine compounds, aliphatic amine compounds, or azonium amine compounds.

[0082] The hole transport layer 6 is formed by, for example, a coating method, a printing method, or a deposition method. Examples of the coating method are a doctor blade method, a bar coating method, a spray method, a dip coating method, or a spin coating method. An example of the printing method is a screen printing method. The hole transport layer 6 may be formed by mixing a plurality of materials, and then pressed or baked. When the hole transport layer 6 includes a low-molecular organic semiconductor or an inorganic semiconductor, the hole transport layer 6 may be formed by a vacuum deposition method.

[0083] (2nd electrode 7) The second electrode 7 is conductive.

[0084] When the solar cell 100 does not include the hole transport layer 6, the second electrode 7 has a property of blocking electrons moving from the photoelectric conversion layer 5 (hereinafter referred to as "electron blocking property"). In this case, the second electrode 7 does not make ohmic contact with the photoelectric conversion layer 5. In this specification, electron blocking property means a property of passing only holes generated in the photoelectric conversion layer 5 and not passing electrons. The Fermi energy level of a material having electron blocking property is lower than the energy level of the conduction band minimum of the photoelectric conversion layer 5. The Fermi energy level of a material having electron blocking property may be lower than the Fermi energy level of the photoelectric conversion layer 5. Examples of materials having electron blocking property are platinum, gold, or carbon materials such as graphene.

[0085] When the solar cell 100 includes a hole transport layer 6 between the second electrode 7 and the photoelectric conversion layer 5, the second electrode 7 does not need to have electron blocking properties. In this case, the second electrode 7 can be made of a material capable of forming an ohmic contact with the photoelectric conversion layer 5.

[0086] (Description of solar cell 200) The solar cell 200 according to the first embodiment is fabricated, for example, as follows.

[0087] First, a conductive substrate having a concave-convex structure and capable of functioning as the first electrode 2 is prepared as the substrate 1. Then, a second electron transport layer 3 is provided on the conductive substrate by, for example, a sputtering method or a spray pyrolysis method. A first electron transport layer 4 is provided on the second electron transport layer 3 by, for example, a spray method or an inkjet method. The first electron transport layer 4 may be prepared using particles of an electron transport material and a binder. The first electron transport layer 4 is prepared at a relatively low temperature, for example, less than 300° C. For the purpose of removing a surfactant attached to the particles, ultraviolet irradiation may be performed instead of a heat treatment. A photoelectric conversion layer 5 is formed on the first electron transport layer 4 by a coating method. The photoelectric conversion layer 5 can also be formed by a physical vapor deposition method or a combination of a physical vapor deposition method and a coating method. A hole transport layer 6 is formed on the first photoelectric conversion layer 5 by, for example, a coating method, a physical vapor deposition method, a chemical vapor deposition method, or the like. Finally, a second electrode 7 is provided on the hole transport layer 6 by a physical vapor deposition method. Examples of coating methods include spin coating, spray coating, die coating, inkjet, gravure coating, flexo coating, and screen printing. An example of physical vapor deposition is sputtering. An example of chemical vapor deposition is deposition using heat, light, plasma, or the like.

[0088] Second embodiment FIG. 4 shows a cross-sectional view of a solar cell 300 according to a second embodiment.

[0089] 4, the solar cell 300 according to the second embodiment has a configuration in which, compared to the solar cell 200 according to the first embodiment, the substrate 1 is not provided, and a recombination layer 21 and a second photoelectric conversion layer 22 are further provided between the first electrode 2 and the second electron transport layer 3. In other words, the solar cell 300 is a stacked solar cell having two photoelectric conversion layers. The matters described in the first embodiment will be omitted as appropriate.

[0090] The second photoelectric conversion layer 22 is provided between the recombination layer 21 and the first electrode 2 .

[0091] The solar cell 300 includes, in this order, a first electrode 2, a second photoelectric conversion layer 22, a recombination layer 21, a second electron transport layer 3, a first electron transport layer 4, a photoelectric conversion layer (first photoelectric conversion layer) 5, a hole transport layer 6, and a second electrode 7.

[0092] Below, configurations that are different from the solar cell 200 will be described.

[0093] A layer having another function may be provided between the first electrode 2 and the second photoelectric conversion layer 22. An example of the layer having another function is a porous layer.

[0094] (Recombination layer 21) In the case of a stacked solar cell such as the solar cell 200, for example, a recombination layer 21 is provided. The recombination layer 21 has a function of taking in and recombining carriers generated in the first photoelectric conversion layer 5 and the second photoelectric conversion layer 22. Therefore, it is desirable that the recombination layer 21 has a certain degree of conductivity. The recombination layer 21 may have, for example, light transmissibility. Light from the visible region to the near infrared region can be transmitted through the recombination layer 21 having light transmissibility. The recombination layer 21 having light transmissibility can be formed from a material that is transparent and has conductivity.

[0095] Examples of such materials are: (i) titanium oxide doped with at least one selected from the group consisting of lithium, magnesium, niobium, and fluorine; (ii) gallium oxide doped with at least one selected from the group consisting of tin and silicon; (iii) gallium nitride doped with at least one selected from the group consisting of silicon and oxygen; (iv) indium-tin composite oxide, (v) tin oxide doped with at least one selected from the group consisting of antimony and fluorine; (vi) zinc oxide doped with at least one of boron, aluminum, gallium, and indium; or (vii) any combination of these It is.

[0096] Examples of materials for the recombination layer 21 include metal oxides such as ZnO, WO3, MoO3, or MoO2, or electron-accepting organic compounds. Examples of electron-accepting organic compounds are organic compounds having a CN group as a substituent. Examples of organic compounds having a CN group as a substituent are triphenylene derivatives, tetracyanoquinodimethane derivatives, indenofluorene derivatives, and the like. An example of a triphenylene derivative is hexacyanohexaazatriphenylene. An example of a tetracyanoquinodimethane derivative is tetrafluoroquinodimethane or dicyanoquinodimethane. The electron-accepting material may be a single compound or may be a mixture of other organic compounds.

[0097] (Second photoelectric conversion layer 22) The photoelectric conversion material constituting the second photoelectric conversion layer 22 has a smaller band gap than the photoelectric conversion material constituting the first photoelectric conversion layer 5. Examples of the photoelectric conversion material constituting the second photoelectric conversion layer 22 include silicon, perovskite compounds, chalcopyrite compounds such as CIGS, and III-V compounds such as GaAs. The second photoelectric conversion layer 22 may contain silicon. When the second photoelectric conversion layer 22 contains silicon, the solar cell 200 becomes a stacked solar cell in which a silicon solar cell and a perovskite solar cell are stacked. However, this is not limited as long as the photoelectric conversion material constituting the second photoelectric conversion layer 22 is a material with a smaller band gap than the photoelectric conversion material constituting the first photoelectric conversion layer 5.

[0098] (Actions and effects of the solar cell 300) The basic action and effect of the solar cell 300 will be described. In the solar cell 300, at least one selected from the group consisting of the first electrode 2 and the second electrode 7 has light transmissivity. When the second electrode 7 has light transmissivity, for example, light is incident on the solar cell 300 from the surface of the second electrode 7. When the solar cell 300 is irradiated with light, the first photoelectric conversion layer 5 absorbs the light and generates excited electrons and holes. The excited electrons move to the first electron transport layer 4 and the second electron transport layer 3. Meanwhile, the holes generated in the first photoelectric conversion layer 5 move to the hole transport layer 6. Furthermore, the light that is not absorbed in the first photoelectric conversion layer 5 passes through the first electron transport layer 4, the second electron transport layer 3, and the recombination layer 21, and is absorbed by the second photoelectric conversion layer 22. The second photoelectric conversion layer 22 absorbs light and generates excited electrons and holes. The excited electrons move to the first electrode 2. On the other hand, holes generated in the second photoelectric conversion layer 22 move to the recombination layer 21. Electrons that have moved from the first photoelectric conversion layer 5 to the recombination layer 21 and holes that have moved from the second photoelectric conversion layer 22 to the recombination layer 21 are recombined in the recombination layer 21. A current is extracted from the first electrode 2 and the second electrode 7, which function as a negative electrode and a positive electrode, respectively.

[0099] (An example of a method for manufacturing the solar cell 300) The solar cell 300 can be fabricated, for example, by the following method. The following method is an example in which the second photoelectric conversion layer 22 is made of silicon.

[0100] First, a second photoelectric conversion layer 22 made of n-type silicon single crystal or the like having an uneven structure is prepared. Then, a first electrode 2 is formed on one main surface of the second photoelectric conversion layer 22 by a coating method, a physical vapor deposition method, a chemical vapor deposition method, or the like. A recombination layer 21 is formed on the other main surface of the second photoelectric conversion layer 22 by a physical vapor deposition method or a vacuum heating vapor deposition method. Then, a second electron transport layer 3 and a first electron transport layer 4 are formed on the recombination layer 21. A first photoelectric conversion layer 5 is formed on the first electron transport layer 4 by a coating method. The first photoelectric conversion layer 5 can also be formed by a physical vapor deposition method or a combination of a physical vapor deposition method and a coating method. A hole transport layer 6 is formed on the first photoelectric conversion layer 5 by a coating method, a physical vapor deposition method, a chemical vapor deposition method, or the like. Finally, a second electrode 7 is provided on the hole transport layer 6 by a physical vapor deposition method. Examples of coating methods include spin coating, spray coating, die coating, inkjet, gravure coating, flexo coating, and screen printing. An example of physical vapor deposition is sputtering. An example of chemical vapor deposition is deposition using heat, light, plasma, or the like.

[0101] The solar cell 300 according to the second embodiment includes two photoelectric conversion layers. That is, the solar cell 300 is a stacked solar cell with a two-layer junction in which two solar cells are joined together. However, the number of joined solar cells is not limited to two, and three or more solar cells may be joined together.

[0102] Third embodiment An embodiment of a photoelectric conversion element according to the present disclosure will now be described.

[0103] The photoelectric conversion element according to the third embodiment has first electrode, a first electron transport layer; second electron transport layer, A photoelectric conversion layer, and second electrode, Equipped with Where: the photoelectric conversion layer is provided between the first electrode and the second electrode, the first electron transport layer is provided between the photoelectric conversion layer and the first electrode, the second electron transport layer is provided between the first electron transport layer and the first electrode, The first electron transport layer includes carbon and a porous electron transport material.

[0104] The photoelectric conversion element according to the third embodiment is, for example, an optical sensor. The photoelectric conversion element according to the third embodiment can function as an optical sensor by, for example, connecting the first electrode and the second electrode with wiring via a current detection device. A known current detection device can be used as the current detection device.

[0105] In the photoelectric conversion element according to the third embodiment, the first electrode may have an uneven structure, as in the solar cell 200 according to the first embodiment. Even if the base material has an uneven structure, the photoelectric conversion layer 5 can be formed to cover the entire surface of the base material with a substantially uniform film thickness. As a result, a highly reliable photoelectric conversion element is obtained in which problems such as short circuiting are unlikely to occur even in the protruding parts. EXAMPLES

[0106] <Example 1> Fig. 5 shows a cross-sectional view of a photoelectric conversion layer-attached substrate 400 according to Example 1. As shown in Fig. 5, the photoelectric conversion layer-attached substrate 400 according to Example 1 includes a substrate 11, a first electrode 12, a second electron transport layer 13, a first electron transport layer 14, and a photoelectric conversion layer 15. The substrate 11, the first electrode 12, the second electron transport layer 13, the first electron transport layer 14, and the photoelectric conversion layer 15 in the photoelectric conversion layer-attached substrate 400 correspond to the substrate 1, the first electrode 2, the second electron transport layer 3, the first electron transport layer 4, and the photoelectric conversion layer 5 in the solar cell 100 and the solar cell 200 according to the first embodiment, respectively.

[0107] The elements constituting the photoelectric conversion layer-attached substrate 400 of Example 1 are as follows. Substrate 11: Silicon substrate with textured structure (average unevenness difference: 2.0 μm, i.e., the average height difference between the convex and concave portions of the textured surface is 2.0 μm) First electrode 12: tin-doped indium oxide layer (thickness: 100 nm) Second electron transport layer 13: TiO2 layer (thickness: 15 nm) First electron transport layer 14: Porous TiO2 layer (thickness: 150 nm) Photoelectric conversion layer 15: A layer mainly containing the perovskite compound CH(NH2)PbI3 A specific manufacturing method is shown below.

[0108] First, a silicon substrate having a tin-doped indium oxide layer formed on its surface was prepared as the substrate 11 and the first electrode 12. The silicon substrate had a textured structure with an average height difference of 2.0 μm in the concave-convex structure.

[0109] Next, a TiO2 film having a thickness of 15 nm was formed as the second electron transport layer 13 on the first electrode 12 by sputtering.

[0110] Next, the second electron transport layer 13 was heated to 150° C. on a stage equipped with a heating device, and the first raw material solution was applied by an inkjet method, and then the surface was cleaned by UV ozone treatment at room temperature to form the first electron transport layer 14. The first raw material solution was a butanol (manufactured by Wako Pure Chemical Industries) dispersion containing 15 g / L of 30-NR-D (manufactured by Great Cell Solar).

[0111] Next, a second raw material solution was applied by spin coating on the first electron transport layer 14 to form a photoelectric conversion layer 15. The second raw material solution was a dimethyl sulfoxide (manufactured by acros) and N,N-dimethylformamide (manufactured by acros) solution containing 0.92 mol / L PbI2 (manufactured by Tokyo Kasei), 0.17 mol / L PbBr2 (manufactured by Tokyo Kasei), 0.83 mol / L formamidinium iodide (manufactured by GreatCell Solar; hereinafter referred to as "FAI"), 0.17 mol / L methylammonium bromide (manufactured by GreatCell Solar; hereinafter referred to as "MABr"), and 0.05 mol / L CsI (manufactured by Iwatani Corporation). The mixing ratio of dimethyl sulfoxide and N,N-dimethylformamide in the second raw material solution was 1:4 (volume ratio).

[0112] In this manner, the photoelectric conversion layer-attached substrate 400 of Example 1 was obtained.

[0113] Of the above-mentioned steps, all steps except for the step for the first electrode 12 were carried out in a dry room in a dry atmosphere having a dew point of −40° C. or less.

[0114] <Comparative Example 1> The comparative example of the substrate with a photoelectric conversion layer 300 was produced in the same manner as in Example 1, except for the following. In producing the first electron transport layer 14, the second electron transport layer 13 was heated to 150°C on a stage equipped with a heating device. Next, the first raw material solution was applied by an inkjet method, and then baked in an oven at 500°C for 30 minutes. Thereafter, the surface was cleaned by UV ozone treatment at room temperature to form the first electron transport layer 14. These points are different from Example 1.

[0115] (TOF-SIMS) Using TOF.SIMS5 (manufactured by ION-TOF, Inc.), mass spectrometry was performed in the depth direction of the substrate in Example 1, which had been subjected to the process up to the formation of the first electron transport layer 14. The measurement conditions were primary ions Bi 3+ (Accelerating voltage 30 kV), sputtering ions Cs + (Accelerating voltage 1 kV), detected secondary ion polarity negative, analysis area 80 μm × 80 μm.

[0116] 6 is a graph showing a carbon profile obtained by TOF-SIMS for the first electron transport layer 14 according to Example 1. A mountainous structure was confirmed in the carbon profile. In Example 1, sufficient carbon was present on the second main surface 2b of the first electron transport layer 14.

[0117] (Relationship between carbon threshold and power generation efficiency) Based on the carbon profile contained in the first electron transport layer 14 revealed by TOF-SIMS, the ratio of the first carbon intensity (a) of the first main surface 14a of the first electron transport layer 14 to the second carbon intensity (b) of the second main surface 14b of the first electron transport layer 14 is defined as the carbon threshold. It is expressed as (carbon threshold)=(intensity b) / (intensity a). The inventors found that the intensity a becomes a constant value in the carbon profile measurement by TOF-SIMS. In addition, it was also confirmed that the carbon concentration of the first main surface 14a of the first electron transport layer 14 becomes a constant value in the surface analysis by X-ray photoelectron spectroscopy (XPS) described below.

[0118] 7A is a graph showing the results of estimating the relationship between the carbon threshold and the normalized efficiency in a solar cell fabricated on a textured substrate having a concave-convex structure on its surface. The inventors have found that if the carbon threshold is 0.41 or more and 1.07 or less, the normalized efficiency is 0.4 or more. They have also found that if the carbon threshold is 0.49 or more and 0.90 or less, the normalized efficiency is 0.8 or more.

[0119] In creating the graph shown in FIG. 7A, an experiment was conducted to determine the relationship between the change in thickness of the porous body of the first electron transport layer 14 and the carbon threshold. As will be described in detail later, as shown in FIG. 9, the difference in film thickness of the first electron transport layer 14 before and after cleaning at 60° C. to 300° C. is proportional to the amount of binder attached to the surface of the first electron transport layer 14, i.e., the carbon threshold, as a first approximation. Also, from the carbon profile of Example 1 shown in FIG. 6, the carbon threshold at 150° C. is estimated to be 0.70. FIG. 7B is a graph showing the relationship between the firing temperature and the carbon threshold.

[0120] The performance of solar cells fabricated on flat substrates at various firing temperatures is shown in Figure 7A and Figures 10A to 10D. In Figure 7A, above the carbon threshold of 0.90, the thickness of the first electron transport layer 14 increases, which can reduce efficiency.

[0121] In texture cells, delamination due to lack of binder can occur in the small carbon threshold range, i.e., below 0.41.

[0122] The carbon threshold of the first electron transport layer 14 is measured by dissolving and removing the perovskite when the perovskite material contains carbon such as organic molecules.

[0123] (XPS) For Example 1, the surface of the substrate 400 that had been subjected to the process of forming the first electron transport layer 14 was analyzed by XPS. The UV irradiation time dependency of the C-C bond peak intensity was measured from the intensity change of the C1s spectrum. FIG. 8 is a graph showing the UV irradiation time dependency of the C-C bond peak intensity obtained from the intensity change of the C1s spectrum obtained by XPS for the first electron transport layer 14 according to Example 1. In Example 1, the C concentration was reduced to the intensity level of Comparative Example 1 by the 30-minute irradiation at which the surface cleaning was completed. It was confirmed that the carbon amount of the first main surface 14a of the first electron transport layer 14 converged to a constant value in the UV ozone cleaning process necessary for forming the photoelectric conversion layer 5.

[0124] (Estimation of the relationship between carbon threshold and power generation efficiency) The relationship between the power generation efficiency and the carbon threshold was complemented for the carbon threshold of Example 1 obtained by TOF-SIMS. After forming the first electron transport layer 14 on the flat substrate, it was baked in an oven at a predetermined temperature for 30 minutes, and then the solvent of the photoelectric conversion layer 15 not containing the perovskite material was spin-coated to obtain the baking temperature dependency of the film thickness of the remaining first electron transport layer 14. FIG. 9 is a graph showing the baking temperature dependency of the film thickness before and after spin-coating the solvent after baking the first electron transport layer 14 arranged on the flat substrate. At the boundary between 250°C and 300°C, the fixing power of the first electron transport layer 14 decreases, and the amount of reduction in film thickness (the difference in the figure) increases.

[0125] The relationship between the temperature dependence of the above film thickness difference and the carbon threshold value from 60°C to 300°C obtained from the carbon profile measurement by TOF-SIMS is shown in Table 1, which corresponds to the temperature dependence by first approximation.

[0126] [Table 1]

[0127] Furthermore, perovskite solar cells were fabricated using the first electron transport layers 14 fabricated at each of the above temperatures, and the power generation performance was compared. The fabrication procedure was as follows.

[0128] (Production procedure) The raw material solution for forming the photoelectric conversion layer was a dimethyl sulfoxide (Acros) and N,N-dimethylformamide (Acros) solution containing 0.92 mol / L PbI2 (Tokyo Chemical Industry Co., Ltd.), 0.17 mol / L PbBr2 (Tokyo Chemical Industry Co., Ltd.), 0.83 mol / L FAI (GreatCell Solar Co., Ltd.), 0.17 mol / L MABr (GreatCell Solar Co., Ltd.), and 0.05 mol / L CsI (Iwatani Corporation). The mixture ratio of dimethyl sulfoxide and N,N-dimethylformamide was 1:4 (volume ratio).

[0129] The raw material solution was applied by spin coating onto the first electron transport layer 14. At this time, 200 μL of chlorobenzene was dropped onto the rotating substrate as a poor solvent.

[0130] Thereafter, the substrate was heat-treated on a hot plate at 115° C. for 10 minutes, and further heat-treated on a hot plate at 100° C. for 30 minutes, thereby forming a photoelectric conversion layer with a thickness of 500 nm on the first electron transport layer 14.

[0131] Thereafter, polytriallylamine (PTAA, manufactured by Sigma-Aldrich Co.) dissolved in toluene was spin-coated onto the photoelectric conversion layer to form a hole transport layer having a thickness of 40 nm.

[0132] Subsequently, a 170 nm thick Au film was deposited on the hole transport layer by vapor deposition to form a second electrode, thus obtaining a perovskite solar cell.

[0133] (Power generation performance evaluation) FIG. 10A is a graph showing the firing temperature dependence of the open circuit voltage of a solar cell fabricated using a flat substrate after firing the first electron transport layer 14 disposed on the flat substrate. FIG. 10B is a graph showing the firing temperature dependence of the short circuit current density of a solar cell fabricated using a flat substrate after firing the first electron transport layer 14 disposed on the flat substrate. FIG. 10C is a graph showing the firing temperature dependence of the fill factor of a solar cell fabricated using a flat substrate after firing the first electron transport layer 14 disposed on the flat substrate. FIG. 10D is a graph showing the firing temperature dependence of the conversion efficiency of a solar cell fabricated using a flat substrate after firing the first electron transport layer disposed on the flat substrate. In FIG. 10A, the open circuit voltage is V oc In FIG. 10B, the short circuit current density is expressed as J sc In FIG. 10C, the fill factor is denoted as FF. In FIG. 10D, the conversion efficiency is denoted as Eff. It was revealed that when the firing temperature is low, the carbon threshold is large, and carbon inhibits the transport of electrons generated in the photoelectric conversion layer. FIG. 11A is a graph showing the results of estimating the solar cell performance when the horizontal axis of FIG. 10A is converted to the carbon threshold and the short circuit between layers occurring in the region where the carbon threshold is low is taken into consideration. FIG. 11B is a graph showing the results of estimating the solar cell performance when the horizontal axis of FIG. 10B is converted to the carbon threshold and the short circuit between layers occurring in the region where the carbon threshold is low is taken into consideration. FIG. 11C is a graph showing the results of estimating the solar cell performance when the horizontal axis of FIG. 10C is converted to the carbon threshold and the short circuit between layers occurring in the region where the carbon threshold is low is taken into consideration.

[0134] The above results are summarized in Tables 2 and 3. The power generation efficiency of the solar cell on the textured substrate is shown in Table 2. The power generation efficiency of the solar cell on the flat substrate is shown in Table 3. The power generation efficiency of the solar cell when fabricated on a uniform film under the conditions of Example 1 was standardized to 1.

[0135] [Table 2]

[0136] [Table 3]

[0137] If the carbon threshold is 0.41 or more, the first electron transport layer 14 has sufficient anchoring power. If the carbon threshold is 1.07 or less, the carbon does not inhibit electron transport, preventing the open circuit voltage, short circuit current density, and fill factor from decreasing. In flat cells, if the carbon threshold is 0.41 or more and 0.90 or less, the cell efficiency is higher. In textured cells, if the carbon threshold is 0.49 or more and 0.90 or less, the cell efficiency is higher. [Industrial Applicability]

[0138] The solar cells of the present disclosure can be used in a variety of applications, including traditional solar cell applications. [Explanation of symbols]

[0139] 1, 11 Board 2, 12 1st electrode 3, 13 Second electron transport layer 4, 14 First electron transport layer 4a, 14a First main surface of first electron transport layer 4b, 14b Second main surface of first electron transport layer 5, 15 Photoelectric conversion layer 6. Hole transport layer 7 Second electrode 21 Recombination layer 22 Second photoelectric conversion layer

Claims

1. a first electrode; a first electron transport layer; a second electron transport layer; A photoelectric conversion layer, and a second electrode, Equipped with Where: the photoelectric conversion layer is provided between the first electrode and the second electrode, the first electron transport layer is provided between the photoelectric conversion layer and the first electrode, the second electron transport layer is provided between the first electron transport layer and the first electrode, the first electron transport layer comprises carbon and a porous electron transport material; the first electron transport layer has a first major surface facing the photoelectric conversion layer and a second major surface facing the second electron transport layer; In the first electron transport layer, a ratio of a second carbon intensity measured by time-of-flight secondary ion mass spectrometry at the second main surface to a first carbon intensity measured by time-of-flight secondary ion mass spectrometry at the first main surface is 0.41 or more and 1.07 or less. Solar cell.

2. The ratio is equal to or greater than 0.49 and equal to or less than 0.

90. The solar cell according to claim 1 .

3. The photoelectric conversion layer contains a perovskite compound. The solar cell according to claim 1 or 2.

4. The electron transport material is titanium oxide. The solar cell according to claim 1 .

5. The first electrode has a concave-convex structure. The solar cell according to claim 1 .

6. The first electron transport layer is in contact with the second electron transport layer. The solar cell according to claim 1 .

7. a first electrode; a first electron transport layer; a second electron transport layer; A photoelectric conversion layer, and a second electrode, Equipped with Where: the photoelectric conversion layer is provided between the first electrode and the second electrode, the first electron transport layer is provided between the photoelectric conversion layer and the first electrode, the second electron transport layer is provided between the first electron transport layer and the first electrode, the first electron transport layer comprises carbon and a porous electron transport material; the first electron transport layer has a first major surface facing the photoelectric conversion layer and a second major surface facing the second electron transport layer; In the first electron transport layer, a ratio of a second carbon intensity measured by time-of-flight secondary ion mass spectrometry at the second main surface to a first carbon intensity measured by time-of-flight secondary ion mass spectrometry at the first main surface is 0.41 or more and 1.07 or less. Photoelectric conversion element.

Citation Information

Patent Citations

  • Organic photoelectric conversion element and manufacturing method therefor

    JP2010161133A

  • Solar power system

    JP2018161044A

  • Solar cell

    JP2020013982A

  • Inorganic-organic hybrid solar cell

    KR1020150122598A

  • Organic thin-film solar cell and organic thin-film solar cell manufacturing method

    WO2014208713A1